The Decalogue on the future of Public Health in Europe (Italian Journal of Public Health, 2008)
The following initiative is being made available to a wider national audience via the document entitled "10 Statements on the Future of Public Health in Europe". This document has been published in several European editions in their respective local languages. The aim of the 10 Statements is to allow a national audience to share the findings of a process of discussions, cultural and scientific exchanges. This process, focusing on the future of public health, began in 2002 within the European Public Health Association (EUPHA). EUPHA is an organization comprised of various public health associations in Europe. EUPHA currently consists of 48 members from 38 different nations and has the participation of more than 10,000 Public Health experts in Europe. This national society network is a tool that helps expand general knowledge about public health problems in Europe, as well as providing an analysis of the different policies and strategies adopted by different countries to address these problems. The Decalogue on the Future of Public Health in Europe is offered simultaneously in English and in Italian on the following journals of Hygiene and Public Health: Annals of Hygiene, Preventive Medicine and Community; - Modern Hygiene - Hygiene and Public Health, - Journal of Preventive Medicine and Hygiene - Italian Journal of Public Health.